Discrimination of the saturated vapours of alcohols by the responses of assembly of piezoquartz sensors covered with metal stearates and their complexes with octadecylamine - Filippov, A.P.; Strizhak, P.E.; Denisyuk, D.I.; Serebry, T.G.; Ivaschenko, T.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The sensitivity of sensor assembly based on piezoquartz resonators (PQR) with the chemical coatings of the specified type relatively to the saturated vapours of several lowest alcohols is investigated. As the chemical coatings, some complex compounds of d-transition metals with stearate anion (St⁻) and octadecylamine (ODA) of the general formula M(ODA)NSt₂ were used, where M²⁺ are ions of d-transition metals Cu(II), Co(II), Ni(II), and N was equal 0, 2, 4, and 6. The sensor images for each of all alcohols investigated by us has the unique character that can be used for discrimination between individual alcohols by using the set of coatings of PQR sensors applied in this work.